Metabolic risk and metabolic dysfunction–associated steatotic liver disease and steatohepatitis in cognitive decline: A retrospective cohort study - Ahmad Basil Nasir; Yassine Kilani; Mohammad Aldiabat; Omar Abdelghany; Youssef Hafez; Nitin Desai; Mahmoud Y. Madi; Francis G. Wade; Kamran Qureshi; Lewis J. Frey; Adam D. Farmer; Wing-Kin Syn (PLoS ONE, 2026)
Objective To determine whether metabolic risk factors (MRFs), metabolic dysfunction–associated steatotic liver disease (MASLD) and metabolic dysfunction–associated steatohepatitis (MASH) are associated with incident mild cognitive impairment (MCI), vascular dementia (VD), and Alzheimer disease (AD). Design Retrospective cohort study using TriNetX (2003–2023) with Propensity score matching. Setting Multicenter, population-based sample from 69 U.S. healthcare organizations in the TriNetX electronic health record. Participants Adults aged ≥50 years with ≥1 outpatient visit and sufficient clinical/laboratory data. Individuals with prior diagnoses of cognitive impairment, cerebrovascular disease, advanced liver disease, malignancy, schizophrenia, or substance use disorders were excluded. Two matched cohorts were constructed: one with 3,546,833 individuals with MRFs and 3,546,833 healthy controls, and another with 525,844 individuals with MASLD/MASH and 525,844 with MRFs only. Matching was based on age, sex, race, and ethnicity. Primary and secondary outcome measures Incident MCI, VD, and AD, identified using ICD-10 codes, assessed at 5–20-year intervals. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using logistic regression. Outcomes were prespecified. Results Among 7,818,146 participants (mean [SD] age, 64.9 [8.8] years; 52.0% female), individuals with MRFs had higher odds of VD (OR, 1.65; 95% CI, 1.63–1.67), MCI (OR, 1.45; 95% CI, 1.42–1.48), and AD (OR, 1.21; 95% CI, 1.19–1.24) vs healthy controls. Compared to the MRF group, individuals with MASLD/MASH had lower odds of VD (OR, 0.86; 95% CI, 0.83–0.89) and AD (OR, 0.83; 95% CI, 0.78–0.88), but higher odds of MCI (OR, 1.37; 95% CI, 1.30–1.44); all p < .001. Conclusions In this large, propensity-matched retrospective cohort study, MRFs were independently associated with significantly increased long-term odds of MCI, VD, and AD. MASLD/MASH demonstrated a divergent cognitive risk profile relative to MRFs alone—characterized by higher odds of MCI but paradoxically lower odds of VD and AD, a pattern that warrants cautious interpretation given potential competing mortality risk, survivor bias, and residual confounding. These findings suggest that MASLD/MASH is associated with a distinct cognitive trajectory, highlighting the importance of early cognitive surveillance in this population.